ANALYSIS OF THE EFFECT OF FIRM SIZE AND EARNINGS PER SHARE ON FINANCIAL DISTRESS DURING THE COVID-19 PANDEMIC IN INDONESIA - Hendrasari, Imung Gutami; Raharja, Surya (Jurnal Apresiasi Ekonomi, 2025)
The Covid-19 pandemic has had a significant impact on many corporations around the world, including Indonesia, since early 2020. This impact is felt in various sectors, especially the economy, where the decline in public consumption has led to a decline in company sales and revenues. This has resulted in uncertainty and financial difficulties, even bankruptcy. This study aims to analyze the effect of company size and earnings per share (EPS) on financial difficulties in non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2021 period.The method used is the Altman's Z-Score model, which is known to be accurate in predicting financial distress. From 780 listed public companies, after a purposive sampling selection process, 281 companies were obtained as samples. Data analysis using binary logistic regression shows that company size has a significant negative effect on financial distress; the larger the company size, the higher the Altman Z-score value, which means the risk of financial distress is lower. However, EPS does not show a significant effect on financial distress, although higher EPS reflects a lower risk of financial distress, this may be because EPS does not sufficiently describe the company's financial condition as a whole.Keywords:Financial Distress, Firm Size, Earnings Per Share